A NEW STABILITY INDICATING UPLC METHOD FOR THE DETERMINATION OF TWO ANTIDIABETIC DRUGS IN COMBINATION: APPLICATIONS TO BULK AND TABLET FORMULATION - PAWAR, A. KRISHNAMANJARI; UNADE, TAREKEGN TADESSE (International Journal of Applied Pharmaceutics, 2022)
Objective: This work was intended to develop a rapid and sensitive stability-indicating ultra-performance liquid chromatographic (UPLC) method for the determination of Metformin and Gliclazide simultaneously in their pharmaceutical bulk and tablet formulation. Methods: Separation was performed on Lunna C18 (100 mm x 2.6 mm, 1.6µ) column by using trifluoroacetic acid buffer: acetonitrile (70: 30, v/v) as a mobile phase at a flow rate of 1 ml/min and a wavelength of detection of 227 nm. Method validation and forced degradation studies were conducted per the respective guidelines of the International Conference on Harmonization. Results: Retention times under the optimized condition were 1.719 min and 2.845 min for Metformin and Gliclazide, respectively. Linearity ranged between 25.0-375.0 µg/ml for Metformin and 4.0-60.0 µg/ml for Gliclazide with a coefficient of determinations (r2) of greater than 0.99. The limit of detection values was 0.25 µg/ml for Metformin and 0.04 µg/ml for Gliclazide. Recovery results ranged from 99.63-101.23 %, and the % RSDs for the precision studies were less than 1.11% for both drugs. The % degradations at various stress conditions ranged from 14.0-5.0% for Metformin and 13.3-2.4% for Gliclazide. The analyte peaks were clearly resolved from the degradant peaks in forced degradation studies. Conclusion: A fast, sensitive and efficient ultra-performance liquid chromatographic method was successfully developed and validated for the concurrent estimation of Metformin and Gliclazide in their combination, and thus the proposed method can be effectively applied for routine quality control works.